INFLUENCE OF THE VENEER QUALITY AND LOAD DIRECTION ON THE STRENGTH PROPERTIES OF BEECH PLYWOOD AS STRUCTURAL MATERIAL FOR FURNITURE (Innovation in Woodworking Industry and Engineering design, 2026)
Plywood is a widely used material in the construction of different furniture types. The production of seating furniture – chairs, armchairs, etc., has the highest share. Knowing plywood’s properties is a prerequisite for its efficient use in the industrial production and improvement of the quality of consumer products. The objective of this study is to evaluate the influence of the veneer quality on the density, bending strength and modulus of elasticity of 20-21 mm thick plywood made of beech veneer. The results showed that the veneer quality does not have an impact on the density, bending strength, and modulus of elasticity. Load direction under bending has a significant influence on the strength and deformation properties. The results of this study will provide an opportunity for optimization of furniture construction made of beech plywood.